Unexpected texture transition induced by grain growth during static annealing of a dilute Mg-1Al alloy - Meng-Na Zhang; Hai-Long Jia; Xiao Ma; Lei Zhao; Zhi-Gang Li; Min Zha (Journal of Magnesium and Alloys)
Conventional rolled Mg-Al alloy sheets typically exhibit strong basal textures that remain and may even strengthen after recrystallization annealing due to the preferential growth of basal-oriented grains, resulting in poor formability at room temperature. Therefore, the knowledge of recrystallization and grain growth is critical for modifying textures of Mg-Al alloy sheets. The static recrystallization and texture evolution in a cold-rolled dilute Mg-1Al (wt.%) alloy during various annealed temperatures ranging from 300 °C to 450 °C, have been investigated using the quasi in-situ electron backscatter diffraction (EBSD) method. The as-rolled Mg-1Al alloy shows a dominant basal texture, which weakens and broadens in the rolling direction (RD) during the subsequent annealing, accompanied by the formation of 〈101¯0〉 texture component. Particularly, the 〈101¯0〉 texture component is more pronounced after annealing at high temperatures. The quasi in-situ EBSD results show that recrystallized grains are mainly induced by shear bands, which exhibit a wide spectrum of orientations with c-axis tilt angles ranging 20°-45° from the normal direction (ND). Orientations of shear band-induced recrystallized grains are retained during the entire recrystallization process, resulting in a reduction in the texture intensity. Moreover, recrystallized grains belonging to the 〈101¯0〉 texture component grow preferentially compared to those with other orientations, which is attributed to low energy grain boundaries, especially grain boundaries with ∼30° misorientation angles. Furthermore, the high temperature annealing facilitates the rapid growth of grain boundaries having a 30° misorientation angle, leading to the occurrence of distinct 〈101¯0〉 texture after annealing at 450 °C for 1 h. The results provide insights for texture modification of rare earth-free low-alloyed Mg alloys by controlling annealing parameters.